Segmenting the eating behaviour of university students using the K-means algorithm - Lenin Quiñones Huatangari; María Alina Cueva Ríos; Rafaela Teodosia Huerta Camones (Institute of Advanced Engineering and Science, 2023)
Universities that teach arts education do not only teach how to play an instrument or conduct musical ensembles; they are agents of change in eating behaviour for the praxis of teaching and dissemination of healthy education. The objective of the research was to segment the eating behaviour of students of the artistic education-music speciality of the National University of Education